An Overview of Justice - Rai, Prithvi Nath (Cognition, 2021)
The term justice is the vaguest relative term or variable which becomes coalesced with the truth from the different philosophical perspectives, economic determinative factors, political identity, religious values, socio-cultural recognition, and the like. As the truth changes; so does the justice. Nothing is permanent in the world. Even the environment changes at its own pace, let alone other superstructures. Due to all those multifarious phenomena, the concept of justice is also found to have been understood relatively and its cycle keeps on moving accordingly as it was in the past, as it is in this present and shall be in the future too accordingly. The objective of this research is to pinpoint an overview of justice in the past and present, which becomes exclusively associated with delivery of justice in the society at large.